1992
DOI: 10.1161/01.atv.12.11.1235
|View full text |Cite
|
Sign up to set email alerts
|

Further characterization of the acetyl LDL (scavenger) receptor expressed by rabbit smooth muscle cells and fibroblasts.

Abstract: We have previously demonstrated that the acetyl low density lipoprotein (LDL), or scavenger, receptor is expressed by rabbit smooth muscle cells (SMCs) and fibroblasts. Moreover, receptor activity in rabbit fibroblasts was regulated over a wide range by preincubating the cells with secretion products from human platelets or with phorbol esters. The current studies were undertaken to examine the regulation of receptor expression in rabbit SMCs, to characterize further the receptor expressed by rabbit SMCs and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

1995
1995
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 33 publications
2
29
1
Order By: Relevance
“…Indeed, smooth muscle cells do take up lipoproteins, as we know now; remnant particles are taken up more avidly than are VLDLs, as shown by Bierman et al (18,19). Under the right conditions, smooth muscle cells can express scavenger receptors (20,21) and take up modified forms of LDL. Still, only a relatively small fraction of the foam cells in the early fatty streak lesion are derived from smooth muscle cells.…”
Section: Early Attempts To Define the Pathogenesis Of Atherosclerosismentioning
confidence: 90%
“…Indeed, smooth muscle cells do take up lipoproteins, as we know now; remnant particles are taken up more avidly than are VLDLs, as shown by Bierman et al (18,19). Under the right conditions, smooth muscle cells can express scavenger receptors (20,21) and take up modified forms of LDL. Still, only a relatively small fraction of the foam cells in the early fatty streak lesion are derived from smooth muscle cells.…”
Section: Early Attempts To Define the Pathogenesis Of Atherosclerosismentioning
confidence: 90%
“…Pitas and colleagues have shown that in vitro cultured human and rabbit smooth muscle cells express low levels of SR-A but that expression can be markedly induced by treatment with phorbol esters or platelet secretion products, resulting in lipid accumulation and foam cell formation. 25,26,47,48 Tumor necrosis factor-␣, interferon-␥, and human cytomegalovirus infection have also been shown to induce expression of SR-A by smooth muscle cells in vitro. 49,50 In contrast, several studies of SR-A expression in human and rabbit atherosclerotic lesions using immunohistochemical and in situ hybridization techniques have failed to show significant receptor expression.…”
Section: Discussionmentioning
confidence: 99%
“…With such techniques it has been shown that in vitro cultured endothelial and smooth muscle cells, in addition to macrophages, have scavenger receptor activity. [25][26][27][28] However, the recent cloning of several receptors with the ability to mediate uptake of modified LDL 29 -33 has meant that the nature of the receptors responsible for these activities is unclear. In this current study, we describe the generation and characterization of high-titer polyclonal antisera against the human SR-A protein by using SR-Adeficient mice.…”
mentioning
confidence: 99%
“…isolated from atherosclerotic lesions, and proposed that these gene expressions may be related to the phenotypic conversion of vascular smooth muscle cells to foam cells in atheromatous lesions (4,9,(44)(45)(46)(47). Furthermore, recent studies have demonstrated that PDGF-BB induces scavenger receptor expression in normal medial smooth muscle cells through protein kinase C activation (9,44) and IFN-y suppresses scavenger receptor activity (33,34).…”
Section: Methodsmentioning
confidence: 99%